If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(a+4)=2(a+3)
We move all terms to the left:
3(a+4)-(2(a+3))=0
We multiply parentheses
3a-(2(a+3))+12=0
We calculate terms in parentheses: -(2(a+3)), so:We get rid of parentheses
2(a+3)
We multiply parentheses
2a+6
Back to the equation:
-(2a+6)
3a-2a-6+12=0
We add all the numbers together, and all the variables
a+6=0
We move all terms containing a to the left, all other terms to the right
a=-6
| y+6-7y=30 | | 4(5x-72)=2(x+54) | | 35=17+y | | 5(4x-6)=14x+6 | | 15y-5=15y+6 | | l+-4=8 | | 9w-8=3w+64 | | 3f=1266 | | ?x4=48 | | 3k−2|=2|k+2| | | 5h=3h-2 | | (3x×2)+36=365 | | 2y=10×-4 | | r-(-2)=10 | | -7x^2-4x=5 | | (5n-3)=12 | | ?=1074x4 | | 8w+4=62 | | 6x+(20+2x)=180 | | 2{x+(2x-1)}=34 | | 4n(2)-3=2n(2)+9 | | -5.5x+0.56=-2.21 | | 7=2+b | | 3/4=3/8y-1/4 | | 3x+4x+5x=165 | | x+(-16)=-16 | | 329-3x=365 | | 21+15=d-17 | | -6(x+1)-4=22 | | .n-25.4=-44.8 | | 2=3h−7 | | -(x+5)+3x=17 |